(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Authors point out serious damages caused to tornato transplantations in the province of Matera by adults of Pleurophorus caesus (Creutzer), at end May beginning June 1994 and 1995. Plants in early stages were rapidly led to death due to the injuries inflicted in the underground portion of the stem by 8-12 individuals per plant. The infestation occurred during the month of June; then adults moved to reproduction places consisting in heaps of manure of herbivores and decaying vegetables, confirming the coprophagous o saprophagous tendency of larval stages. The Authors give biologica! and ethological news about the species and suggest eventual interventions in order to carry out a control in the phytophagous phase.